The Impact of Land Use and Land Cover Change on Water Quality in Lake Victoria Catchment: A Case Study of Nkangabile River at Nyegezi Bay, Tanzania - Mashafi, Charles A; Mabula, Makemie; Semba, Masumbuko; Ezekiel, Charles N; Kashindye, Benedicto; Salehe, Mwanahamisi A; Mrosso, Hillary DJ; Kayanda, Robert; Kimirei, Ismael A (Tanzania Journal of Science, 2024)
Understanding the trends and impacts of anthropogenic activities in the water basins and catchments is key to the effective management and conservation of aquatic environments. This study analyses the land use and land cover (LULC) changes in the Nkangabile catchment and their impacts on water quality in the Nyegezi Bay of Lake Victoria, Tanzanian side. GIS and Remote sensing techniques were used to analyze the multi-temporal changes in LULC that occurred in the past 30 years from 1983 to 2013, split into four epochs of 10-year intervals. The changes in LULC were analyzed using image differencing and cross-tabulation for pairwise methods. The results indicated an increasing deterioration of water quality and a considerable transformation of LULC between the four epochs and more so in the long-term period from 1983 to 2013. The study provides evidence that LULC changes are accelerated by anthropogenic activities that severely affect the ecosystem through increased water pollution. Balancing human activities through proper land use planning as well as conservation awareness are strongly recommended to ensure adequate protection of the Lake Victoria ecosystem.